4(x+2)=3(2x-(6-x))

Simple and best practice solution for 4(x+2)=3(2x-(6-x)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=3(2x-(6-x)) equation:


Simplifying
4(x + 2) = 3(2x + -1(6 + -1x))

Reorder the terms:
4(2 + x) = 3(2x + -1(6 + -1x))
(2 * 4 + x * 4) = 3(2x + -1(6 + -1x))
(8 + 4x) = 3(2x + -1(6 + -1x))
8 + 4x = 3(2x + (6 * -1 + -1x * -1))
8 + 4x = 3(2x + (-6 + 1x))

Reorder the terms:
8 + 4x = 3(-6 + 2x + 1x)

Combine like terms: 2x + 1x = 3x
8 + 4x = 3(-6 + 3x)
8 + 4x = (-6 * 3 + 3x * 3)
8 + 4x = (-18 + 9x)

Solving
8 + 4x = -18 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
8 + 4x + -9x = -18 + 9x + -9x

Combine like terms: 4x + -9x = -5x
8 + -5x = -18 + 9x + -9x

Combine like terms: 9x + -9x = 0
8 + -5x = -18 + 0
8 + -5x = -18

Add '-8' to each side of the equation.
8 + -8 + -5x = -18 + -8

Combine like terms: 8 + -8 = 0
0 + -5x = -18 + -8
-5x = -18 + -8

Combine like terms: -18 + -8 = -26
-5x = -26

Divide each side by '-5'.
x = 5.2

Simplifying
x = 5.2

See similar equations:

| 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 | | 50-8x-4=18 | | 50-8x-5=18 | | 50-8x-6=18 | | 50-8x-12=18 | | 50-8x-11=18 | | 50-8x-13=18 | | 50-8x-14=18 |

Equations solver categories